Semiotic Analysis: Decoding Signs and Messages on Grand Filano YouTube Ads - I Wayan Januartha; Ni Nyoman Deni Ariyaningsih (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
In the rapidly evolving digital advertising landscape, understanding how semiotic elements function is crucial for creating effective advertisements. A deep understanding of semiotics is essential for grasping how advertisements convey complex meanings to their audiences. While semiotic analysis is commonly applied in advertising, there is still a gap in understanding how signs and messages in digital commercials work together to create meaning. This study explores the interpretation of signs and messages in the Grand Filano YouTube advertisement by applying Saussure's semiotic theory (Lepschy, 1985), (Barthes, 1977), and Wierzbicka’ (1996). The goal is to uncover how these semiotic elements combine to communicate meaningful messages. This research employs a qualitative approach, using direct observation to collect data from the Grand Filano YouTube ad. The data collection involved observing and categorizing written text, slogans, visuals, colors, and non-verbal communication. The findings reveal that the Grand Filano advertisement effectively integrates these components to convey complex messages. The signs carry both denotative and connotative meanings that enhance the ad's impact. For instance, vibrant colors convey energy and confidence, while neutral tones suggest purity and luxury. The study concludes that the combination of signs and messages generates powerful meanings and influences the audience. This research provides practical insights for marketers, highlighting the strategic use of color and symbolism to craft more persuasive and engaging advertisements.